If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x * 3) = 184 Reorder the terms for easier multiplication: x + (3x) = 184 Combine like terms: x + (3x) = 4x 4x = 184 Solving 4x = 184 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = 46 Simplifying x = 46
| -8(1+4b)=-8(7b+4)+7b | | 8(3r-5)=-8(-2-2r) | | 8(x-8)+8x=-8(4-6x) | | 5x=6x+70 | | 3x-7=4x-5 | | ((17/25)/3/5(-4))/1/5+1/2 | | -3(b+1)=-4(2+b) | | ((17/25)/3/5-4)/1/5+1/2 | | -3(6+1)=-4(2+b) | | -3(6+1)=-4(2+6) | | 8x+7.46=4x+14 | | 8.6a+9.11=-32.17 | | 0.5x+12.6=x-6.8 | | 3x*2y= | | 0.7x+6.67=-0.2x+7.17 | | 2w^4+7w+32=0 | | 2(1-6n)+1=3(1-5n) | | 4C^2+C+7.9956=0 | | 100=2(4w-5)+2w | | -8(4+7x)=8(2-x) | | (w-2/w+6)+1=w+2/w+3 | | 3x-(-4)=72 | | -3=.2x-3.6 | | 6n-8(n-7)=6(-6n-2) | | (17/25)/3/5 | | (n+4)/(4n+8)+1/(n^2+2n) | | -7(3-x)=-7+6(x-2) | | 13=7+1/2 | | 13=7+.5 | | -2(7+3a)+a=-7(a+2) | | 1-15/a=6 | | y+2z=18 |